Critical and practical reflections on the legal regime of national and cross-border change of the address of the minor - Valverde Martínez, María José (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The change of domicile of the minor within the Spanish territory or to another country is one of the most frequent conflicts between parents who jointly exercise parental authority. With regard to these controversies, it is irrelevant if the parents are divorced, were in fact partners or never lived together. Nevertheless, as a fundamental decision that affects the minor’s interest, the transfer of his / her domicile cannot be unilaterally decided by one parent. It requires the agreement of both parents. Failing that, a judicial authorization is required prior to a minor’s domicile change. This study focuses on is the legal rules governing the minor’s transfer of domicile both under Spanish domestic law and in private international law. The Order of October 9, 2019 rendered by the Court of Appeal of Barcelona is one of the most useful examples to look into the different steps of the minor’s change of domicile form a legal perspective.
Keywords: change of domicile of the minor; parental authority; private international law; child abduction; voluntary jurisdiction